Kierkegaard as humanist : discovering my self - Come, Arnold B. (Arnold Bruce), 1918- (McGill-Queen's studies in the history of ideas, 1995)
The self is the central and unifying theme of Soren Kierkegaard's writings. In Kierkegaard as Humanist, Arnold Come provides a comprehensive exposition of Kierkegaard's understanding of what it means to be a self and the problems and possibilities that every human being faces in the task of becoming a self. Come limits his discussion to the humanist dimensions of Kierkegaard's writings - to what is open to the experience of every human being without reference to or assistance from any particular religious insight or revelation. He concludes that Kierkegaard's ontology is independent of his Christian theology but includes an openness to and a relation with the eternal as inherent natural possibility in the experience of every human being.